OFR-37-82 Potential Effect Of Ferrous Scrap Composition Changes On The Quality Of Iron And Steel Castings - W. L. Swager (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Tramp (undesirable) elements introduced into iron and steel castings via purchased ferrous scrap are evaluated as to their likely degree of future threat to the quality of castings. Conclusions are based on analysis of literature and on nonmail surveys of foundries, scrap processors, trade and technical associations, and others. The existing tramp-element problem is expected to be persistent, but amenable to improved control by foundries and their suppliers. Four recommendations for action are given.